2004
DOI: 10.1212/01.wnl.0000125188.79106.29
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of circulating trace amines in primary headaches

Abstract: Whereas the elevation of plasma trace amine levels in both migraine and CH supports the hypothesis that disorders of biogenic amine metabolism may be a characteristic biochemical trait in primary headache sufferers, the observation that such alterations are more prominent in patients with CH than migraine patients suggests that they may reflect sympathetic or hypothalamic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 28 publications
2
48
2
Order By: Relevance
“…Taking in mind that hypothalamus contains the maximal concentration of trace amines and their receptors, we measured plasma levels of tyramine, octopamine, synephrine and dopamine in CH patients in remission and active periods. All patients, in the two phases of the disease, showed very high levels of trace amines and DA in plasma and platelets [30,60]. All these results suggest that also in CH patients is present an anomaly of tyrosine metabolism.…”
Section: Elusive Amines and Chmentioning
confidence: 69%
See 1 more Smart Citation
“…Taking in mind that hypothalamus contains the maximal concentration of trace amines and their receptors, we measured plasma levels of tyramine, octopamine, synephrine and dopamine in CH patients in remission and active periods. All patients, in the two phases of the disease, showed very high levels of trace amines and DA in plasma and platelets [30,60]. All these results suggest that also in CH patients is present an anomaly of tyrosine metabolism.…”
Section: Elusive Amines and Chmentioning
confidence: 69%
“…This hypothesis is also supported by the evidences that in such areas of CNS TAARs, g-protein receptors activated by elusive amines, and dopamine receptors are abundantly distributed. Their activation may be related to the high levels of DA, octopamine and synephrine found in plasma and platelets of migraine without aura sufferers during headache-free periods [30,31].…”
Section: Glutamate and Auramentioning
confidence: 99%
“…A study on patients with cluster-type headache and migraine found increased plasma levels of biogenic amines (especially tyramine, octopamine, and synephrine). Therefore, more research is warranted to determine the role of biogenic amines in headache (38). Although some biogenic amines have been associated with headache, no studies to date have provided an evidence base.…”
Section: Biogenic Aminesmentioning
confidence: 99%
“…The TA 1 receptor has not been directly linked with any pathophysiological process, although trace amines are known to be associated with the hypertensive "beer, wine, and cheese effect" and are thought to play a role in psychiatric disorders such as schizophrenia (O'Reilly et al, 1991) and depression (Boulton, 1980;Premont et al, 2001) as well as primary headache (D'Andrea et al, 2004). Modulation of trace amine systems may be a potential therapeutic avenue (Branchek and Blackburn, 2003;Berry, 2007), particularly because the receptors are likely to be amenable as drug targets (Davenport, 2003).…”
Section: Pathophysiological Rolementioning
confidence: 99%